2011
DOI: 10.1002/humu.21608
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of human nter and cterBRCA1mutations using growth and localization assays in yeast

Abstract: A large number of missense mutations have been identified within the tumor suppressor gene BRCA1. Most of them, called "variants of unknown significance" (VUS), cannot be classified as pathogenic or neutral by genetic methods, which complicates their cancer risk assessment. Functional assays have been developed to circumvent this uncertainty. They aim to determine how VUS impact the BRCA1 protein structure or function, thereby giving an indication of their potential to cause cancer. So far, three relevant assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(62 citation statements)
references
References 45 publications
7
54
0
1
Order By: Relevance
“…This indicates that at least one of the two endogenous NLSs of BRCA1 is functional in yeast. It also confirms our previous results using the deficient nucleoporin Nup49-GFP construct, which revealed that an active transport of BRCA1-mCherry from the cytoplasm towards the nucleus is necessary for nuclear aggregation (Millot et al, 2011). NLS inactivation completely impaired this mechanism, resulting in cytoplasmic aggregation.…”
Section: The Human Brca1 Protein Aggregates In Yeast Cellssupporting
confidence: 91%
See 4 more Smart Citations
“…This indicates that at least one of the two endogenous NLSs of BRCA1 is functional in yeast. It also confirms our previous results using the deficient nucleoporin Nup49-GFP construct, which revealed that an active transport of BRCA1-mCherry from the cytoplasm towards the nucleus is necessary for nuclear aggregation (Millot et al, 2011). NLS inactivation completely impaired this mechanism, resulting in cytoplasmic aggregation.…”
Section: The Human Brca1 Protein Aggregates In Yeast Cellssupporting
confidence: 91%
“…5A). The Y1853X nonsense mutation results in the loss of the ten C-terminal amino acids of BRCA1, which destabilizes the BRCT structure (Williams et al, 2001) and delocalizes the full-length BRCA1 aggregation into the cytoplasm in yeast cells (Millot et al, 2011). Strikingly, both W1837C and Y1853X mutations strongly impaired the nuclear localization of the Nter-NLS-Cter peptide (Fig.…”
Section: Misfolding Induces Cytoplasmic Delocalization In the Absencementioning
confidence: 94%
See 3 more Smart Citations